Economic Development and Renewable Energy Nexus in Morocco: Co-Integration and Causality - Benyetho, Yousra; El Attar, Abdelilah (Finance & Economics Review, 2023)
Purpose The present study explores the causal relationships between economic development, renewable energy consumption, nonrenewable energy consumption, and CO2 emissions in the context of Morocco. Methods The panel unit root test, Auto Regressive Distributed Lag (ARDL), and bounds test were used to assess the co-integration of the variables in the study and the long-run relationship between them. It employs the Granger causality test using a vector error correction model to determine the existence and direction of causality among the variables. It uses Morocco's annual statistical data from 1990 through 2019. Results The co-integration of the variables in the study was confirmed, implying that a long-run relationship exists between them. The causality test results suggest that a bidirectional causality exists between renewable energy consumption and economic development, which validates the feedback hypothesis of the mutual link between renewable energy consumption and economic development. Implications These findings suggest that Morocco's economic development is critical in providing the required resources for sustainable development. It also implies that boosting renewable energy utilization would enhance Morocco's economic development and limit environmental degradation.